Expression of S100A Alarmins in Cord Blood Monocytes Is Highly Associated With Chorioamnionitis and Fetal Inflammation in Preterm Infants - Golubinskaya, Veronika; Puttonen, Henri; Fyhr, Ing-Marie; Rydbeck, Halfdan; Hellström, Ann; Jacobsson, Bo; Nilsson, Holger; Mallard, Carina; Sävman, Karin (Frontiers in Immunology, 2020)
Preterm infants exposed to chorioamnionitis and with a fetal inflammatory response are at risk for severe neonatal morbidities and adverse outcome. Alarmins S100A8, S100A9, and S100A12 are expressed by myeloid cells and have been associated with inflammatory activation and monocyte modulation. Aim: To study S100A alarmin expression in cord blood monocytes from term healthy and preterm infants and relate results to clinical findings, inflammatory biomarkers and alarmin protein levels, as well as pathways identified by differentially regulated monocyte genes. Cord blood CD14+ monocytes were isolated from healthy term (n=10) and preterm infants (< 30 weeks gestational age, n=33) by MACS technology. Monocyte RNA was sequenced and gene expression was analysed by Principal Component Analyses and hierarchical clustering. Pathways were identified by Ingenuity Pathway Analysis. Inflammatory proteins in cord blood were measured by Multiplex ELISA, and plasma S100A proteins by mass spectrometry. Histological chorioamnionitis (HCA) and fetal inflammatory response syndrome (FIRS) were diagnosed by placenta histological examination. S100A8, S100A9 and S100A12 gene expression were significantly increased and with a wider range in preterm vs term infants. High S100A8 and S100A9 gene expression (n=17) within the preterm group was strongly associated with spontaneous onset of delivery, HCA, FIRS and elevated inflammatory proteins in cord blood, while low expression (n=16) was associated with impaired fetal growth and physician-initiated delivery. S100A8 and S100A9 protein levels were significantly lower in preterm vs term infants, but within the preterm group high S100A gene expression, spontaneous onset of labor, HCA and FIRS were associated with elevated protein levels. 1900 genes were differentially expressed in preterm infants with high vs low S100A alarmin expression. Analysis of 124 genes differentially expressed in S100A high as well as FIRS and HCA groups identified 18 common pathways and S100A alarmins represented major hubs in network analyses. High expression of S100A alarmins in cord blood monocytes identifies a distinct clinical risk group of preterm infants exposed to chorioamnionitis and with a fetal inflammatory response. Gene and pathway analyses suggest that high S100A alarmin expression also affects monocyte function. The connection with plasma S100A protein levels and monocyte phenotype warrants further investigation.